2022
DOI: 10.3390/ijerph192416442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Health Behaviors of Higher Education Students in Ghana: A Cross-Sectional Study

Abstract: Stressful events can significantly impact health behaviors of tertiary students in various ways. Many studies reported adverse alterations in health behaviors during the COVID-19 pandemic. However, there is limited knowledge about students from sub-Saharan African countries. Therefore, this study aimed to assess effects of the COVID-19 pandemic on the health behaviors of Ghanaian tertiary students, with an emphasis on the association between sleep and other health behaviors. A cross-sectional study with eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Our findings showed that every student in the research experienced stress in varying degrees, and that about six out of every 10 students experienced stress induced by COVID-19 pandemic. This finding is similar to earlier studies in China [34][35][36] and Ghana [37][38][39][40]. Collectively, these findings suggest that COVID-19 pandemic resulted in elevated levels of stress among university students across the globe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings showed that every student in the research experienced stress in varying degrees, and that about six out of every 10 students experienced stress induced by COVID-19 pandemic. This finding is similar to earlier studies in China [34][35][36] and Ghana [37][38][39][40]. Collectively, these findings suggest that COVID-19 pandemic resulted in elevated levels of stress among university students across the globe.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding is further buttressed by an earlier study which suggested that higher GAD levels among students were due to the inability to cope well with the challenges that came with COVID-19 [46]. Additionally, another study indicated that COVID-19 pandemic made a significant negative impact on mental health among university students [39,40,47]. COVID-19 changed education dramatically in Ghana and across the globe, whereby teaching is undertaken either in restricted classroom environment or remotely on digital platforms [6,7].…”
Section: Discussioncontrasting
confidence: 58%
“…Many studies suggest that the pandemic affected negatively food consumption patterns and diets, especially during the period of lockdown [48,53]. However, other studies posit that attention to health and healthy diets, especially those presumed to boost the immune system, increased during the pandemic [59,60,67,72].…”
Section: Agriculture Subsectors and Food Chain Stagesmentioning
confidence: 99%
“…Concerning food utilisation, the focus of the studies is mainly on diet quality and dietary diversity, and food safety. The pandemic affected diet quality with a reduction in the consumption of many health-enhancing products [60,112] as well as an increase in the use of unhealthy foods [60] and alcohol [53]. This, as well as the reduction in physical activity/exercise especially during the lockdown [53], caused an increase in the prevalence of non-communicable diseases.…”
Section: Impacts On Food Security and Nutritionmentioning
confidence: 99%
See 1 more Smart Citation